1994
DOI: 10.1073/pnas.91.7.2378
|View full text |Cite
|
Sign up to set email alerts
|

Lyme disease: a growing threat to urban populations.

Abstract: Lyme disease or Lyme bobrosis, which is caused by three groups of the spirochete Borreiia burgdorferi, Is Asi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 72 publications
0
57
0
6
Order By: Relevance
“…Changes in housing development and land use practices such as suburban sprawl encroachment into wildlife habitat as well as the reforestation of cropland and shrinking of areas available for hunting have led to the explosive growth of deer and rodent populations in many parts of the United States. This deer population increase has been associated with the spread of Lyme disease and other tick-borne infections for which deer serve as reservoir hosts (56). Similarly, fluctuations of tick and mosquito abundance may affect the human risk of vector-borne diseases (22).…”
Section: Wildlife and Vector Population Fluctuationsmentioning
confidence: 99%
“…Changes in housing development and land use practices such as suburban sprawl encroachment into wildlife habitat as well as the reforestation of cropland and shrinking of areas available for hunting have led to the explosive growth of deer and rodent populations in many parts of the United States. This deer population increase has been associated with the spread of Lyme disease and other tick-borne infections for which deer serve as reservoir hosts (56). Similarly, fluctuations of tick and mosquito abundance may affect the human risk of vector-borne diseases (22).…”
Section: Wildlife and Vector Population Fluctuationsmentioning
confidence: 99%
“…B. burgdorferi sensu lato is pathogenic spirochaete bacterium, at least 15 genospecies belonging to B. burgdorferi sensu lato complex (Postic et al 2007) are known, but only five genospecies -B. burgdorferi sensu stricto, B. garinii, B. afzelii, B. bissettii and B. spielmanii are considered to be the etiological agent for human Lyme borreliosis (Richter et al 2004). Lyme borreliosis is the most common tick-borne disease in Eurasia (O'Connell et al 1998) and North America (Steere 1994). …”
Section: Introductionmentioning
confidence: 99%
“…An expanded analysis, which included 39 different human Lyme disease patients, revealed that a combination of the OspE and ElpB1 lipoproteins could be the basis for a new serodiagnostic assay for Lyme disease. Importantly, this novel serodiagnostic test would be useful independent of prior OspA vaccination status.Lyme disease, the most common arthropod-borne disease in North America (49,50,70), is a multisystem disorder characterized by dermatologic, cardiac, neurologic, and arthritic manifestations (68, 69). Lyme disease pathogenesis and Borrelia burgdorferi infectivity have been studied in numerous animal models; however, the disease manifestations observed vary widely among host species (9).…”
mentioning
confidence: 99%
“…Lyme disease, the most common arthropod-borne disease in North America (49,50,70), is a multisystem disorder characterized by dermatologic, cardiac, neurologic, and arthritic manifestations (68, 69). Lyme disease pathogenesis and Borrelia burgdorferi infectivity have been studied in numerous animal models; however, the disease manifestations observed vary widely among host species (9).…”
mentioning
confidence: 99%